El regreso de la Segunda Guerra Mundial ‘In Our Time’: post-memoria, historia y narración en The Soldier’s return y Son of War de Melvyn Bragg - Howes, Christina (Revista de Filología Románica, 2017)
This paper examines how Melvyn Bragg, British journalist, broadcaster and writer, portrays the aftermath of World War Two on family and community in The Soldier’s Return (1999) and Son of War (2001). I contend that Bragg’s apparently simplistic and minimalist style approximates what Michael Rothberg (2000) terms as traumatic realism. By blending the ordinary and the domestic with the extraordinary, he manages to evoke a meaningful absence and traumatic undertones at the same time as resonating with historical ‘truth’. Thus, I conclude that through the tension between an outer naivety and underlying disturbances, Bragg’s post-memorial discourse achieves a public disclosure which hitherto remained, primarily, in the intimate realm of postwar family life.